Stock market response to COVID-19, containment measures and stabilization policies: The case of Europe - Jens Klose; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2022)
Policymakers imposed constraints on public life in order to contain the Covid-19 pandemic. At the same time, fiscal and monetary policy implemented a large range of of expansionary measures to limit the economic consequences of the pandemic and stimulate the recovery. In this paper, we assess the response of the equity market as a high-frequency indicator of economic activity to containment and stabilization policies for 29 European economies. We construct indicators of containment and stabilization policies and estimate a range of panel VAR models. The main results are threefold: First, we find that stock markets are highly responsive to containment and stabilization policies. We show that domestic fiscal policy as well as monetary policy support the recovery as reflected in the stock market. Second, expansionary fiscal policy conducted at the European level reduces rather raises stock prices. Third, we estimate the model over subsamples and show that the counter-intuitive stock market response to EU policies is driven by the responses in medium- and high-debt countries. These countries' stock markets are also particularly susceptible to monetary policy announcements.
Keywords: E44; E52; E62; 330; Covid-19; Europe; stabilization policies; lockdown-measures; panel VAR